Jednotka pro energetické využití kontaminováné biomasy - Votava, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Cílem práce je vytvoření předběžných návrhových výpočtů pro určení rozměrů, hmotnosti a tlakové ztráty jednotlivých uzlů čištění spalin kontaminované biomasy. První část práce je věnována definici biomasy jako paliva, legislativnímu určení množství povolených emisí a jejich popisu. Dále jsou v práci představeny zařízení na čištění spalin a jejich stručný popis. Praktická část se věnuje tvarovým návrhům, určení základních rozměrů několika typů kontaktorů doplněné o výpočty hmotností a tlakových ztrát těchto aparátů. V poslední části jsou jednotlivé varianty řešení porovnávány mezi sebou.

The purpose of the thesis is to create preliminary design calculations to determine dimensions, weights and pressure losses of individual contaminated biomass combustion gas treatment nodes. The first part of the thesis deals with the definition of biomass as a fuel, legislative determination of allowed emissions and their description. Then the systems for combustion gas treatments are discussed given their brief description. The practical part focuses on shape designs, determining base dimensions of each type. Weights and pressure losses of individual versions are computed too. In the last part the individual versions are solved with real values and compared to each other.
Unit for utilization of contaminated biomass for energy production
Keywords: látkový filtr; katalytická filtrace; čištění spalin; spalování biomasy; fabric filter; catalytic filtration; flue gas cleaning; biomass burning